Making a Better World from the Children’s Perspective: How to Make Compassion Contagious - Sugianto, Mona; Abidin, Zainal; Purwono, Urip; Siregar, Juke (Opción, 2019)
Compassion is recognized as one of the answers to create a better world, es- pecially due to its role in reducing the suffering and burden of fellow human beings. Children have unique perspectives and ways to play a role in making a better world. The purpose of this study was to describe from the perspec- tive of children, how compassion can be contagious in social life. A qualitative phenomenological approach was chosen to understand the experience of 629 subjects aged 12 to 18 years (Mean=14.88 years; 396 girls; and 233 boys), which obtained by the convenience sampling technique. Data were processed using the thematic analysis method. The results of this study have illustrat- ed that there are two major parts that are important to consider to make compassion contagious. The first part is things that need to be done, namely helping others, starting to be compassionate to others, loving others, caring more for others, respecting each other, building positive awareness and char- acter of ourselves, improving our relationships with God, becoming example of compassion itself for other children, the willingness to give, forgive, and work together. The second part contains things that should not be done if you want compassion to be contagious and spread in life, that is, you should not discriminate others, stop being selfish, stop being hostile to others, and stop all types of bullying behavior and oppression. So, the spreading of compassion is a must to create a better world. To spread compassion, children possess an excellent way by helping people in suffering and be compassionate. Children have a genuine way; they do not demand and wait for the other party to start the compassionate action. They start it from themselves, with the simple thing they can do, and do it spontaneously as soon as it is needed.